Impact of Environmental Factors on Seed Germination and Seedling Emergence of White Clover (Trifolium repens L.) - Lei Chu; Yiping Gao; Lingling Chen; Patrick E. McCullough; David Jespersen; Suraj Sapkota; Muthukumar Bagavathiannan; Jialin Yu (Agronomy, 2022)
White clover (Trifolium repens L.) is cultivated as a forage crop and planted in various landscapes for soil conservation. There are numerous reports of failed white clover stands each year. A good understanding of the seed germination biology of white clover in relation to environmental factors is essential to achieve successful stand establishment. A series of experiments were conducted to investigate the impacts of light, temperature, planting depth, drought, and salt stress on seed germination and the emergence of white clover. White clover is negatively photoblastic, and seed germination averaged 63 and 66% under light and complete dark conditions 4 weeks after planting (WAP), respectively. Temperature affected the seed germination speed and rate. At 1 WAP, seeds incubated at 15 to 25 °C demonstrated a significantly higher germination rate than the low temperatures at 5 and 10 °C; however, the germination rate did not differ among the temperature treatments at 4 WAP. The results suggest that white clover germination decreases with increasing sowing depths, and the seeds should be sown on the soil surface or shallowly buried at a depth ≤1 cm to achieve an optimal emergence. White clover seeds exhibited high sensitivity to drought and salinity stress. The osmotic potential and NaCl concentration required to inhibit 50% seed germination were −0.19 MPa and 62.4 mM, respectively. Overall, these findings provide quantifiable explanations for inconsistent establishment observed in field conditions. The results obtained in this research can be used to develop effective planting strategies and support the successful establishment of white clover stands.